Learner performance at the School of military justice (SoMJ) - Make, Maria Mmotsi (My University, 2014)
The first key to wisdom is this - constant and frequent questioning, for by doubting, we are led to question and by questioning we arrive at the truth (Pierre Peter Aberlard). lll The purpose of this study is, to investigate possible contributory factors to poor learner1 performance at the School of Military Justice (SoMJ) on Advanced Military Law Course, the trend that was noticed after the implementation of Outcome-Based Education (OBE) in 2009. The determination of the nature of challenges that might contribute negatively to learner performance at SoMJ will be concluded. My hypothesis is that since the accreditation of SoMJ as a service provider and implementation of OBE, a trend of poor learner performance has been noticed. This might impact negatively on the South African National Defence Force (SANDF) and ultimately poor performance at the workplace. A qualitative method was used, the reason being qualitative method will describe social reality from the point of vlew of participants within the system studied as well as supported by the relevant data collected. A qualitative phenomenological method to prove the hypothesis of this study was conducted. One-on-one semi-structured interviews corroborated by analysis of document relevant to the research questions and the concept of study was used. The study explored the perceptions and experiences of twenty seven volunteer learners who attended the Advanced Military Law Course during 2010, 2011, 2012, the specialists from the management group and facilitators in terms of the research questions. As demonstrated by data collection and data analysis processes, five themes emerged, namely global view of changing approaches to education, South African view of changing education approaches, Military Education, traditional learning versus OBE and contributory factors to learner performance (adult learning) .The findings of the study revealed that there is actually a high rate of incompetence after the first assessment attempt. A lot of factors that might contribute to poor learner performance were identified and investigated. Recommendations based on the findings of the study will guide the Defence Legal Services Division (DLSD) on measures to improve the current learner performance at SoMJ.
Thesis (M.M. (Security))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2013.
Keywords: Learner performance; Outcome-Based Education; South Africa